myo-Inositol-1-phosphate Synthase Is Required for Polar Auxin Transport and Organ Development - Chen, Hao (American Society for Biochemistry and Molecular Biology, 2010)
myo-Inositol-1-phosphate synthase is a conserved enzyme that catalyzes the first committed and rate-limiting step in inositol biosynthesis. Despite its wide occurrence in all eukaryotes, the role of myo-inositol-1-phosphate synthase and de novo inositol biosynthesis in cell signaling and organism development has been unclear. In this study, we isolated loss-of-function mutants in the Arabidopsis MIPS1 gene from different ecotypes. It was found that all null mips1 mutants are defective in embryogenesis, cotyledon venation patterning, root growth, and root cap development. The mutant roots are also agravitropic and have reduced basipetal auxin transport. mips1 mutants have significantly reduced levels of major phosphatidylinositols and exhibit much slower rates of endocytosis. Treatment with brefeldin A induces slower PIN2 protein aggregation in mips1, indicating altered PIN2 trafficking. Our results demonstrate that MIPS1 is critical for maintaining phosphatidylinositol levels and affects pattern formation in plants likely through regulation of auxin distribution.